Multiple intracranial aneurysm embolization in a single session - Vargas-Urbina, John F. (2023)
Objective: To determine clinical and angiographical outcomes in patients with multiple intracranial aneurysms who underwent endovascular therapy in a single session. Materials and Methods: Patients older than 18 years with multiple (≥2) ruptured or non-ruptured aneurysms were included, and all of them underwent endovascular therapy in a single session between 2019 and 2021. Clinical and angiographic data was collected. Immediate occlusion and follow-up data were collected. Rankin modified scale was used for assessing clinical outcomes. Results: Twenty-five patients were treated, and fourteen had subarachnoid hemorrhage. Seventy-eight aneurysms were diagnosed, and 59 of them were treated. The most frequent location was at the ophthalmic segment. Maximum average height was 5.2- mm, which showed significant statistical difference with a ruptured condition (p≤0.02). The main modality for endovascular therapy was the remodeling technique, which was used in 39% of all cases. Immediate Raymond Roy staging was I in 60% of all cases, and IIIa in 35% of all cases. Complication rate was 24%, and mortality rate was 8%. Conclusions: Single session endovascular therapy is an effective and safe option for cases of multiple intracranial aneurysms in our institution. Occlusion and complication rates were acceptable.